Implementasi Teory Transaction Cost Economics (TCE) Dalam Kebijakan Antitrust Prespektif Islam - Yayan Nasikin; Eka Putri Innayah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
In economic studies, Islam lays down fundamental principles that are global in nature. Often competition between business entities is seen as an obstacle for business people, but it is an unavoidable interaction. In competition, imperfect competition behavior often occurs by carrying out monopoly actions. To that end, the government issues an antitrust policy to regulate and promote healthy competition in the economic ecosystem. The application of Theory Transaction Cost Economics (TCE) in antitrust policies is important in order to produce a healthy rule of law. In the Islamic view, this is urgent as an effort to analyze the background and objectives of the company's integration both vertically and horizontally so that errors in the application of antitrust law do not occur.